Diagnosis and treatment of acute coronary syndrome during the novel coronavirus infection COVID-19 pandemic - A. M. Namitokov; O. P. Ishevskaya; V. I. Fetisova; E. D. Kosmacheva; V. A. Porkhanov (Российский кардиологический журнал)
The novel coronavirus infection COVID-19 pandemic has spread to more than 180 countries. Cardiovascular patients belong to one of the susceptible population cohorts. There is a peculiar pathogenesis and variety of clinical manifestations of COVID-19, as well as difficulties with early diagnosis. Other unresolved issues are routing, surgery and therapy of such patients and comorbidities. Due to absence of well-defined algorithms and guidelines, the treatment of patients with acute coronary syndrome (ACS) in different countries is carried out differently. Interactions between antiviral and coronary artery disease medications are also not completely clear. Based on the available data, the main organizational and therapeutic approaches for ACS during the COVID-19 pandemic are reflected.